Trends Of Cancer Admissions At Kasturba Medical College Hospital, Manipal - Udaya Kiran N; Chakladar B.K; Mallya Prema V (Wolters Kluwer Medknow Publications, 1989)
Hospital records of kasturba medical college hospital, manipal, Karnataka from 1975 through 1986 were analyzed for cancer admissions. The study period was grouped into two halves. A significant rising trend of proportional case rate of cancer admissions was observed between the two halves. When the cancer trends by site was studied, a rising trend was seen only in cancers of breast, lung, bladder and colorectal region, whereas a declining trend was noted in cancers of orpharyngeal region and that of the uterine cervix. There was a general male predominance in all cancer cases with M.F. ratio of 1.6. In males the most common type of cancer was of the oropharyngeal region and in females, of the uterine cervix.